Earnings surprises and prior insider trading: Tests of joint informativeness* - ALLEN, STEVEN; RAMANAN, RAMACHANDRAN (Contemporary Accounting Research, 1990)
Abstract. Building on the notion that both earnings surprises and the level of insider trading are noisy signals of future prospects of the firm, this paper empirically investigates joint informativeness of the two signals surrounding earnings announcements. Classification of a large sample of firms in the time period 1977–81 based both on the levels of earnings surprise and insider trading results in a finer partition informationally, compared to using just one signal. Both additive and interactive effects are observed while analysing the security market response during the three trading days centered on the day of earnings announcements. Over a 19‐day postannouncement period, the results are less pronounced. The overall pattern of results implies that each signal may contain information not contained in the other, and/or some of the noise associated with each signal may be interactively resolved at the time of earnings announcements. This inference is robust under many measurement alternatives. Résumé. À partir du principe voulant que les bénéfices imprévus ainsi que l'importance des opérations d'initiés soient des indicateurs manifestes des perspectives futures de l'entreprise, les auteurs procèdent à une étude empirique de la qualité informative conjointe des deux indicateurs dans le cadre des avis de bénéfices. La classification d'un vaste échantillon d'entreprises pendant la période 1977–1981 en fonction à la fois du niveau des bénéfices imprévus et de l'importance des opérations d'initiés permet un découpage plus subtil sur le plan informationnel que l'utilisation d'un indicateur unique. Les auteurs observent les effets tant additifs qu'interactifs de cette classification dans l'analyse de la réponse du marché boursier au cours des trois jours de bourse centrés sur le jour de la communication des avis de bénéfices. Pour la période de 19 jours suivant la période d'avis, les résultats sont moins accusés. Le modèle global des résultats suppose que chaque indicateur peut livrer de l'information que l'autre ne livre pas et qu'une partie de ce que manifeste chaque indicateur peut être résolue de façon interactive au moment de la communication des avis de bénf́ices. Cette induction résiste à l'épreuve de plusieurs techniques de mesure.